Superplasticity and High Strength in Al–Zn–Mg–Zr Alloy with Ultrafine Grains. Issue 1 (21st August 2019) - Valiev, Ruslan Z.; Kazykhanov, Vil U.; Mavlyutov, Aydar M.; Yudakhina, Anna A.; Chinh, Nguyen Q.; Murashkin, Maxim Yu
Abstract : Herein, the ultrafine‐grained (UFG) 7xxx series alloy Al–4.8Zn–1.2Mg–0.14Zr demonstrates superplasticity at unusually low temperatures of 120–170 °C while maintaining its high‐strength state. The UFG structure is formed by high pressure torsion (HPT) at room temperature (RT), which leads to a considerable increase in the strength characteristics by ≈60% compared with the material after conventional heat treatment T6. It is found that the UFG alloy exhibits thermostability when testing or annealing up to 170 °C. Deforming by tensile test at a strain rate of 10 −4 s −1 and 10 −3 s −1, the elongation to failure at 120 and 170 °C exceeds 250% and 500%, respectively, whereas the strain rate sensitivity reaches 0.45, which is a typical value characterizing superplastic deformation. After superplastic deformation, the UFG alloy maintains 25–50% higher strength characteristics at RT than that after conventional heat treatment T6. The origin of such superior behavior of the UFG alloy is discussed. Abstract : Herein, the ultrafine‐grained (UFG) 7xxx series Al alloy processed by severe plastic deformation demonstrates superplasticity (SP) at unusually low temperatures of 120–170 °C while maintaining its high‐strength state. After SP deformation, the UFG alloy maintains 25–50% higher strength characteristics at room temperature than that after standard treatment T6. The origin of such superior behavior of the UFG alloy is discussed.